DESAIN APLIKASI PEMBUATAN SERTIFIKAT PRAKERIN PADA DIVISI HUMAN CAPITAL PT. KRAKATAU IT CILEGON BERBASIS WEBSITE - Ofah Musyarrofah; Sumiyati Sumiyati; Dian Novita (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
PT. Krakatau Information Technology is a Krakatau Steel Group company based on Electronic Data Processing (EDP) Human Capital Division is a division at PT. Krakatau Information Technology has the task of providing / recruiting employees according to company needs, and this division carries out the task of accepting and guiding work practice participants in accordance with their vocational training work in the industrial worldafter the participants have attended the training for 30 days or 3 months, participants will get a certificate as a sign of carrying out industrial work practices, in the Human Resources Department, PT Kitech's division of making certificates for Industrial Work Practices activities at present is still conventional by using Microsoft Excel and Microsoft Publiser software to manage certificates. The process of making certificates takes a long time to make and there are still many staff who cannot manage and print certificates properly.To overcome this problem, a system was designed that could help to do the job quickly and precisely so as to facilitate the printing of certificates. In designing this system the tools used include Flowmap, Unified Modeling Language (Use Case Diagrams, Class Diagrams, Squence Diagrams, Activity Diagrams), Relationships Between Tables, File Structures, Design of Input Output and Software used are MySQL and Web-based applications, The results of this study are the application of certificates used to facilitate the Human Capital Division in accelerating certificate printing to be more effective and efficient.